Pengaruh Anticipatory Guidance Terhadap Pertumbuhan Dan Perkembangan Bayi Usia 0-6 Bulan - Atik Pramesti Wilujeng; Desi Trianita; Ninis Indriani (Jurnal Keperawatan Muhammadiyah, 2020)
The Toddlerhood is an important period in the process of human growth and development. Development and growth in that period became a determinant of the success of children's growth and development in the next period. Early life of children starts from parents, so parents are responsible for the child's future. This study aims to analyze the influence of providing Anticipatory Guidance on the growth and development of infants aged 0-6 months. This study uses a quasi experimental design with a post test only non equivalent control group design. The respondents involved in this study were 54 mothers who had babies aged 0-6 months who were taken using a purposive sampling technique which was divided into treatment and control groups. The results of the Mann-Whitney U test showed that there were differences in growth in the treatment group with the control group with a value of Ï = 0.009 while the results of the Mann-Whitney U test on the development variable showed a difference between the treatment group with the control group with a value of Ï = 0.021. Assessment of infant growth is carried out by measuring anthropometrics which include weight (BW), length / height (TB), and head circumference then compared with the WHO-NCHS BB / U index. Assessment of infant development using KPSP (Kuesioner Pra Skrining Perkembangan). Anticipatory guidance is an educational method provided to provide guidance to parents so that children can grow and develop optimally and aims to improve family independence in maintaining health, preventing and overcoming child health problems.